2013
DOI: 10.1007/s00784-013-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fluoride dentifrice (5,000-ppm) on caries-related plaque and salivary variables

Abstract: The 5,000-ppm F toothpaste could be regarded as a possible effective regimen against caries in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The plaque index in the group with 5,000 F was significantly reduced compared to the group with 1,100 ppm F Mannaa et al 2014a To measure the effects of a toothpaste containing 5,000 ppm F on caries-related factors in dental plaque and saliva 6 weeks longitudinally on mothers with an average age of 38.4 years (n = 17) and 17 teenagers with an average age of 14.5 years (n = 17) Sampling of approximal fluid for fluoride analysis and approximal plaque for organic acid analysis was performed Counts of cariogenic microorganism were performed at each of 4 visits Six weeks' use of toothpaste containing 5,000 ppm F significantly increased the approximal fluid F concentration (p < 0.05) Changes in interproximal plaque acidogenicity were noted, including significant reductions in AUC (5.7 and 6.2, respectively) and maximum pH fall and an increase in minimum pH (p < 0.05) A significant increase in the salivary buffer capacity and a reduction in the salivary mutans streptococci were observed (p < 0.05) Mannaa et al 2014b To assess the caries risk following 6 weeks' use of toothpaste containing 5,000 ppm F using 'Cariogram' software 6 weeks longitudinally on 17 mothers with an average age of 38.4 years (n = 17) and teenagers with an average age of 14.5 years (n = 17) Mutans streptococci and lactobacilli counts were performed at each of 4 visits A statistically significant linear trend was observed for mutans streptococci counts (p < 0.01) and the number of subjects with a salivary concentration of mutans streptococci <10 3 increased at each visit; the same trend was also observed for lactobacilli and buffer capacity scores (p = 0.04 and p = 0.03, respectively)…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The plaque index in the group with 5,000 F was significantly reduced compared to the group with 1,100 ppm F Mannaa et al 2014a To measure the effects of a toothpaste containing 5,000 ppm F on caries-related factors in dental plaque and saliva 6 weeks longitudinally on mothers with an average age of 38.4 years (n = 17) and 17 teenagers with an average age of 14.5 years (n = 17) Sampling of approximal fluid for fluoride analysis and approximal plaque for organic acid analysis was performed Counts of cariogenic microorganism were performed at each of 4 visits Six weeks' use of toothpaste containing 5,000 ppm F significantly increased the approximal fluid F concentration (p < 0.05) Changes in interproximal plaque acidogenicity were noted, including significant reductions in AUC (5.7 and 6.2, respectively) and maximum pH fall and an increase in minimum pH (p < 0.05) A significant increase in the salivary buffer capacity and a reduction in the salivary mutans streptococci were observed (p < 0.05) Mannaa et al 2014b To assess the caries risk following 6 weeks' use of toothpaste containing 5,000 ppm F using 'Cariogram' software 6 weeks longitudinally on 17 mothers with an average age of 38.4 years (n = 17) and teenagers with an average age of 14.5 years (n = 17) Mutans streptococci and lactobacilli counts were performed at each of 4 visits A statistically significant linear trend was observed for mutans streptococci counts (p < 0.01) and the number of subjects with a salivary concentration of mutans streptococci <10 3 increased at each visit; the same trend was also observed for lactobacilli and buffer capacity scores (p = 0.04 and p = 0.03, respectively)…”
Section: Discussionmentioning
confidence: 87%
“…concentration in plaque after the use of 5,000 ppm toothpaste reached the level of around 14 ppm F, while the corresponding value after the use of toothpaste with 1,450 ppm F was around 10 ppm. Mannaa et al [2014a, b] even found that the pH dropped less after rinsing with 10% sucrose solution when tooth brushing was performed using 5,000 ppm toothpaste compared to toothpaste with 1,450 ppm F. Thus, even though the fluoride concentration in plaque does not reach 10 ppm for a longer period, it seems that the higher concentration of fluoride changes the cariogenic potential in the plaque, perhaps by decreasing the number of lactate-forming microorganisms [Mannaa et al 2014b], which then results in the pH not dropping so low after a cariogenic rinsing in 10% sucrose. This may also explain that Lynch et al [2000], Baysan et al [2001] and found lower plaque scores after the use of 5,000 ppm toothpaste compared to toothpaste with 1,450 ppm F ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is reported to be significantly associated with the widespread use of fluoride (F − ) toothpaste (Walsh, Worthington, Glenny, Marinho, & Jeroncic, ). It is known that a toothpaste with higher fluoride concentration has a greater effect in preventing dental caries (Mannaa et al, ; Walsh et al, ). Although the prevalence of dental caries has decreased, the interproximal surface is still a high‐risk site of dental caries (Haak, Wicht, Hellmich, Gossmann, & Noack, ).…”
Section: Introductionmentioning
confidence: 99%
“…Little is however known on the long-term impact of such fluoride-based programs on oral bacteria. It is generally thought that a low-fluoride exposure can interact with the consecutive cycles of de- and remineralization while higher fluoride concentrations may hamper bacterial acid production [7, 8]. A reduced pH-drop would favour the growth of health-associated bacteria that prefer pH values around neutrality rather than the acid-producing and acid-tolerating species associated with caries [9].…”
Section: Introductionmentioning
confidence: 99%